Anomalously large magnetic moment in nanocrystalline Co0.3Zn0.7Fe2O4 thin films. (17th October 2017) - Prabhu, R; Sahu, B N; Venkataramani, N; Prasad, Shiva; Krishnan, R
Abstract: Co0.3 Zn0.7 Fe2 O4 nanocrystalline thin films were deposited by pulsed laser ablation technique on amorphous quartz substrate. These films were as deposited at different substrate temperatures ( T S ) varying from room temperature (RT) to 750 °C. The RT deposited films were ex situ annealed at annealing temperatures ( T A ) ranging from 150 °C to 750 °C. The magnetic properties of the films were observed to depend on T A and T S . A spontaneous magnetization (4 π M S ) value higher than that of the bulk was observed in the as deposited film at T S = 750 °C. This film also showed a higher Curie temperature than bulk. These results were explained based on the grain growth and cation distribution in thin films.